(untitled) (Circe de clásicos y modernos, 2018)
As on a person’s psychology, there are in the pólis two opposing principles, passions and law. In gregarious animals, there is also a political factor that leads many individuals to work for a common purpose. But in man there is a difference in his political activity, i.e., the law that comes from reason and cannot be expressed without words. For this reason, Aristotle, unlike Plato, gives a constructive function to Sophists, as experts on rhetoric, which is necessary to establish law in the city. Politics is a superior science that articulates ethics and rhetoric in order that men in the city can reach the ultimate goal, happiness. For Aristotle, there is not an external metapolitical objective, which could separately satisfy the upper components of the human psyche.